Perbandingan efektifitas talcum, unguentum, dan pasta ekstrak terstandar kulit manggis (garcinnia mangostana linn) terhadap ringworm disease (tinea corporis) - Miranti Candrarisna (VITEK : Bidang Kedokteran Hewan, 2016)
Purpose of this study was to compare the effectiveness of talcum, unguentum and paste of mangosteen peel extract standardized (Garcinnia mangostana Linn) against Ringworm Disease in vivo. This type of experimental research using completely randomized design. The research sample: male hamster 24 animals, divided 4 groups and 6 replications: a control group, were infected ringworm fungus (Trycophyton mentagophytes) but not given treatment (P0), the treatment group infected ringworm fungus and treated with talcum extract standardized mangosteen rind (P1) treatment group and the untreated ringworm fungus infected unguentum standardized extract of mangosteen peel (P2), a group that ringworm fungus infected and treated with a paste of mangosteen peel extract standardized (P3). Giving a fungal infection ringworm done once, then wait 1-2 weeks until the fungal infection spread to the whole body of experimental animals were then treated according to the treatment dose of 50% twice a day. Observation of wound healing, change in body surface area that has been infected with mildew, scab and reduction of area small dots such as rings and mushrooms are native examination conducted on the 5th, 10th and 15th. Results of the examination of the wound healing, change in body surface area that has been infected with mildew, scab and reduction of area small dots like ring diskoring and analyzed by Analysis of Variance (ANOVA). The results showed: the treatment group was given a fungal infection ringworm and treated with a paste of mangosteen peel extract standardized to 50% dose twice daily (P3) provide most excellent and effective than the group P2, P1 and P0 appears on the 15th day.